Analysis of the Effect of Product and Price on Purchasing Decisions at Jaya Murni Gold Shop in Sintang Regency - Romeo Anarchy Setyawan; Sumiyati Sumiyati (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the effect of product and price on purchasing decisions at Jaya Murni Gold Shop in Sintang Regency. The research uses a quantitative associative approach with a case study conducted at a single gold shop. Primary data were obtained through interviews with the owner and the distribution of Likert-scale questionnaires to 100 consumers selected using a purposive sampling technique. Secondary data include the number of gold shops in Sintang Regency, price lists per gram based on gold purity levels, and annual sales revenue data. Data analysis was carried out using validity tests, reliability tests, classical assumption tests, and multiple linear regression using SPSS. The results show that simultaneously, product and price have a significant effect on purchasing decisions (F count 8.511; sig. 0.000). Partially, price has a positive and significant effect on purchasing decisions, while product does not have a significant effect. The R² value of 0.149 indicates that the two variables only explain 14.9% of the variation in purchasing decisions, while 85.1% is influenced by other factors outside the model. These findings confirm that gold consumers at Jaya Murni Gold Shop are more sensitive to price aspects than product aspects. Practically, shop management needs to focus strategies on competitive and transparent pricing, accompanied by product management as a supporting factor. Future research is suggested to include variables such as store image, service quality, and trust, as well as to expand the object to several gold shops so that the depiction of gold purchasing behavior becomes broader and more in-depth.